L’11 settembre nella poesia italiana (Altre Modernità, 2011)
The paper studies some Italian poems dedicated to the events of September 11th. A connection between formal analysis and application of categories of the cultural studies (orientalism, gender, post-human) reveals some costants in the description of the towers fall. On the formal level, it is possible to identify, in some texts, regular verses and quotations from works of the literary tradition. Some poems focus on the power relations between East and West; other poems go beyond the opposition organic/inorganic or renogotiate the human category by the inclusion of the literary character of the vampire.